2007
DOI: 10.1038/nature05473
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic occupancy and lineage-specific transcriptional control of rRNA genes by Runx2

Abstract: Regulation of ribosomal RNA genes is a fundamental process that supports the growth of cells and is tightly coupled with cell differentiation. Although rRNA transcriptional control by RNA polymerase I (Pol I) and associated factors is well studied, the lineage-specific mechanisms governing rRNA expression remain elusive. Runt-related transcription factors Runx1, Runx2 and Runx3 establish and maintain cell identity, and convey phenotypic information through successive cell divisions for regulatory events that d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
271
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 217 publications
(285 citation statements)
references
References 30 publications
14
271
0
Order By: Relevance
“…Furthermore, Runx2 up-regulation does not impede cell-cycle progression in cancer cells. In contrast, in normal osteoblasts, Runx2 ablation accelerates proliferation and increases ribosomal gene expression (18,19,29,30). Together these observations indicate that Runx2 may function as a tumor suppressor in some cell types and have oncogenic potential in others.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…Furthermore, Runx2 up-regulation does not impede cell-cycle progression in cancer cells. In contrast, in normal osteoblasts, Runx2 ablation accelerates proliferation and increases ribosomal gene expression (18,19,29,30). Together these observations indicate that Runx2 may function as a tumor suppressor in some cell types and have oncogenic potential in others.…”
mentioning
confidence: 71%
“…Runx2, p53, and pRb all control cell proliferation by regulating cell-cycle progression and mediating cell growth through effects on ribosomal biogenesis (18,19,30,37,38). Abrogation of tumor suppressor pathways controlled by p53 and pRb, which are ubiquitously expressed, results in the development of diverse tumors that are confined to specific tissues (7,8), indicating that lineagespecific mechanisms are involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(7) The involvement of RUNX2 as a regulator of osteoblast proliferation also was consistent with data obtained in other biologic contexts. (8)(9)(10)(11) More recently, Zaidi and colleagues (12) proposed that RUNX2 functions as a tumor suppressor in primary diploid osteoblasts, whereas Eliseev and colleagues (13) suggested that RUNX2 acts as a proapoptotic factor.…”
Section: Introductionmentioning
confidence: 99%
“…Our data is consistent with other reports showing that there is a large increase in pre-rRNA transcript in G 2 with decreases in G 1 . 5,46 Another report done in yeast has found that the levels of rRNA transcript peaks following replication late in S phase. 4 However, this increase during S phase was only two fold, suggesting it may be due to the duplication of the genome, while we observe a 3-4 fold increase.…”
Section: Resultsmentioning
confidence: 99%